Growth analysis in the potato crop under different irrigation levels - Netto, Antenor de Oliveira Aguiar; Rodrigues, João Domingos; Pinho, Sheila Zambello de (Pesquisa Agropecuaria Brasileira, 2000)
An experiment was carried out at Fazenda São Manoel, pertaining to the Faculdade de Ciências Agronômicas of the Universidade Estadual Paulista, São Manuel, SP, Brazil, to evaluate irrigation levels in the potato (Solanum tuberosum ssp. tuberosum) growth, cv. Aracy. This work was installed in a sandy Dark-Red Latosol, under a plastic cover. The experimental design was an entirely randomized block composed by irrigation in the potato plots when the soil water potential has reached 15, 35, 55, 75 and 1,500 kPa, and five plant sampling time with four replicates. It was found that higher irrigation levels led to increase of the leaf area index, leaf area duration, relative growth rate and net assimilation rate.